The evolvement of mechanical properties and microstructure of commercial aluminum alloy 6061 via high-pressure torsion - Cheeranan Krutsuwan Nuphairode; Intan Fadhlina Mohamed; Fauziana Lamin; Wan Fathul Hakim Wan Zamri; Mohd Zaidi Omar; Horita, Zenji (Penerbit Universiti Kebangsaan Malaysia, 2020)
A precipitation-hardened AA6061 alloy is processed by high-pressure torsion (HPT) technique which has demonstrated its success in refining grain structures up to the nanometer-scale. With the aim of upscaling the strengthen lightweight materials for larger applications, this study is essential to analyse the related strengthening mechanisms for further strengthening potential and microstructure alteration on sample with extra diameter size. This severe plastic deformation (SPD) technique simultaneously contributes to an intensification of dislocation density which caused by the grain refinement. This study presents properties enhancement of 30mm diameter of AA6061 alloy after being compressed at 4GPa pressure and subjected to a 0.2 rpm torsional force for 1 and 3 turn(s) at room temperature. For the result testing, Vickers microhardness, tensile test, X-ray diffraction (XRD) and Transmission electron microscopy (TEM) were used as to analyse the mechanical properties as well as the microstructure changes. As a result, grain structures were refined to 200nm, and its mechanical properties, such as tensile strength and hardness is enhanced to ±600MPa and ±172HV, respectively. The homogeneity of hardness is increased with the number of turns or the torsional strain applied. For this particular aluminium alloy, the grain refinement and grain boundary hardening were identified as the main hardening mechanisms by the process of HPT.